Finite element analysis of maxillary orthodontic therapies with variable alveolar bone grafts under occlusal forces in patient with unilateral cleft lip and palate - Zhang, Zhi; Li, Chenghao; Zheng, Qian; Shi, Bing; Liu, Renkai (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: To investigate the biomechanical effects of maxillary orthodontic treatment on different alveolar bone grafting positions loaded with occlusal forces in an unilateral cleft lip and palate (UCLP) patient. Methods: Finite element analysis was employed to simulate clinical scenarios more accurately by loading with occlusal forces on 8 bone-grafted models during maxillary orthodontic treatment. Displacement and von Mises stress pattern during maxillary protraction, expansion, and combined protraction and expansion were analyzed.. Results: The seven bone-grafted models exhibited significantly smaller horizontal displacements at the non-cleft side landmarks during maxillary protraction and expansion compared to non-bone grafted models. Additionally, alveolar cleft bone grafted in the upper 1/3 and middle 1/3 exhibited greater asymmetry displacement and stress under maxillary protraction and expansion. Conclusion: The study highlights the necessity of considering occlusal forces in finite element study on orthodontic therapies for UCLP patients. The upper 1/3 and middle 1/3 bone graft conditions may require secondary bone graft supplementation to ensure the effectiveness of maxillary orthodontic treatment.